13. The Intersection of Mathematics and Language in the Post-Secondary Environment: Implications for English Language Learners - Jean Choi; Rebecca Milburn; Brett Reynolds; Philip Marcoccia; Patrick Justin Silva; Sikander Panag (Collected Essays on Learning and Teaching, 2013)
Given the increasing number of English Language Learners (ELLs) in post-secondary environments (Roessingh & Douglas, 2012), educational practices such as availability of language support for mathematics should be assessed to ensure that all students’ needs are met. To explore the effects of language on mathematics in ELLs, mathematical test items were presented in four language contexts: vocabulary knowledge, negation, preposition use, and atypical sentence structure. Sixty students enrolled in mathematics courses volunteered to complete the mathematics task. Results suggest that math items falling into each of the four language contexts disadvantage ELLs, highlighting that the needs of ELLs should be considered at all levels, from classroom practices to educational policy.